The nucleus as a condensate of monopole and quadrupole pairing vibrations - Broglio, R. A.; Maglione, E.; Sofía, H. M.; Vitturi, A. (North Holland Publishin Co., 1982)
Fil: Broglio, R. A. The Niels Bohr Inslitute, University of Copenhagen; Dinamarca